2020
DOI: 10.4155/fmc-2020-0224
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of post-translational Modifications and Coactivators of STAT6 Signaling in Tumor Growth and Progression

Abstract: Signal transducers and activators of transcription 6 (STAT6) are highly expressed in various tumors and associated with tumorigenesis, immunosuppression, proliferation, metastasis and poor prognosis in human cancers. In response to IL-4/13, STAT6 is phosphorylated, dimerizes and triggers transcriptional regulation after recruitment of coactivators to transcriptosome, such as CBP/p300, SRC-1, PARP-14 and PSF. Post-translational modifications, including phosphorylation, ubiquitination, ADP-ribosylation and acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 125 publications
0
12
3
Order By: Relevance
“…STAT6 plays a role in tumorigenesis, immunosuppression, proliferation, and metastasis of human cancers. The highly activated IL‐4/IL‐4Ra/STAT6 signaling in prostate cancer stem cell‐like cells validates the tumorigenic activity of STAT6 26 . However, the results of these studies contradict our findings.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…STAT6 plays a role in tumorigenesis, immunosuppression, proliferation, and metastasis of human cancers. The highly activated IL‐4/IL‐4Ra/STAT6 signaling in prostate cancer stem cell‐like cells validates the tumorigenic activity of STAT6 26 . However, the results of these studies contradict our findings.…”
Section: Discussioncontrasting
confidence: 76%
“…Sultan et al demonstrated that STAT5A induces E‐cadherin and promotes β‐catenin binding to the cell surface through E‐cadherin‐mediated linkage, thereby inhibiting human breast cancer cells 8 . In another study, increased expression of IL‐4/STAT6 signaling was associated with reduced tumor volume and weight, as well as the increased expression of apoptotic proteins 26 . However, the role of STAT5 in promoting tumor development has also been documented.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between aberrant STAT6 activity/expression levels and the size of the PAs suggested that overactivation of STAT6 increased the risk of developing MACs as opposed to MICs. Previous studies have shown that STAT6 is associated with the tumorigenesis, immunosuppression, proliferation, metastasis and poor prognosis of human cancers [ 17 ]. For example, STAT6 activation promotes the malignant behavior of colon cancer, prostate cancer, breast cancer and mediastinal large B-cell lymphoma cells [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Available online at: https://www. accessdata.fda.gov/scripts/opdlisting/oopd/detailedIndex.cfm?cfgridkey=668818 28 Clinicaltrials.gov Available online at: https://clinicaltrials.gov/ct2/show/ NCT04322708 through the action of Janus family (JAKs) tyrosine kinases (Huang et al, 2020). It acts as a Th2-inducing transcriptional activator (Goenka and Kaplan, 2011) and is implicated in the immunity to helminths and in the pathophysiology of various allergic conditions (Karpathiou et al, 2021).…”
Section: Transcription Factors the Signal Transducer And Activator Of Transcription 6 Pathwaymentioning
confidence: 99%
“…IL-4 and IL-13, together with IL-3, IL-15, IL-33, IFNα and platelet-derived growth factor-PDGF, can activate STAT6 through the action of Janus family (JAKs) tyrosine kinases ( Huang et al, 2020 ). It acts as a Th2-inducing transcriptional activator ( Goenka and Kaplan, 2011 ) and is implicated in the immunity to helminths and in the pathophysiology of various allergic conditions ( Karpathiou et al, 2021 ).…”
Section: Focus On Type 2 Inflammation: the Protagonistsmentioning
confidence: 99%